An exploration of desired abstinent and non-abstinent recovery outcomes among people who use methamphetamine - Alex Elswick; Amanda Fallin-Bennett; Karen L. Roper; Evan Batty; Christopher J. McLouth; William Stoops; Hilary L. Surratt; Carrie B. Oser (Harm Reduction Journal)
Abstract Background In the United States, complete abstinence persists as the standard for demonstrating recovery success from substance use disorders (SUDs), apart from alcohol use disorder (AUD). Although the FDA has recently indicated openness for non-abstinence outcomes as treatment targets, the traditional benchmark of complete abstinence for new medications to treat SUDs remains a hurdle and overshadows other non-abstinent outcomes desired by people with SUDs (e.g., improved sleep, employment, family reunification). This study sought to expand the definition of recovery to include non-abstinent pathways by exploring non-abstinence-based outcomes desired by people who use methamphetamine (PWUM). Methods Participants (n = 100) were recruited from existing National Institute on Drug Abuse (NIDA) projects including a treatment-seeking sample of people recently released from prison (all of whom endorsed recent methamphetamine use) and a sample of people using syringe service programs. In a convergent survey design, participants responded to closed-ended questions regarding recovery outcomes, followed by open-ended items to gain a better understanding of PWUM and their conception of recovery. The importance of non-abstinent outcomes was measured in five categories (substance use, physical health, cognitive functioning, mental health, and financial/social/relationships). Results Participants were primarily White (88%), male (67%), and an average age of 40. Approximately two-thirds of participants agreed that people need to stop all mood- or mind-altering substances to be in recovery (64%). Nevertheless, participants indicated a variety of desired non-abstinent recovery outcomes, both substance-related (e.g. reductions in methamphetamine use) and non-substance-related (e.g. improved economic stability). Specific non-abstinent outcomes endorsed as “absolutely essential” by PWUM included: preventing legal trouble (92%), employment stability (82%), improved quality of life (80%), housing stability (78%), improved coping skills (78%), improved relationships (75%), economic/income stability (74%), ability to think clearly (73%), less impulsivity (73%), less depression (71%), less stress (70%), improved hopefulness (70%), and improved sleep (70%). Open-ended responses emphasized employment stability, economic/income stability, improved coping skills, improved relationships, as well as improved energy, appetite, and sleep. Conclusion Our findings indicate the importance of non-abstinent recovery outcomes among PWUM, suggesting high acceptability of non-abstinent recovery targets by people with lived experience. Further, the essential importance of non-abstinent outcomes, especially in the financial/social/relationship and mental health domains, were highlighted, providing novel targets for delivering SUD treatment/recovery.